2015
DOI: 10.1097/md.0000000000001450
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Exercise Training on Diastolic and Systolic Function After Acute Myocardial Infarction

Abstract: After acute myocardial infarction (AMI), diastolic dysfunction is frequent and an important determinant of adverse outcome. However, few interventions have proven to be effective in improving diastolic function. We aimed to determine the effect of exercise training on diastolic and systolic function after AMI.One month after AMI, 188 patients were prospectively randomized (1:1) to an 8-week supervised program of endurance and resistance exercise training (n = 86; 55.9 ± 10.8 years) versus standard of care (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 38 publications
(54 reference statements)
3
22
0
3
Order By: Relevance
“…This stems from the fact that, although there are currently numerous parameters of potential interest in the prognostic assessment after an AMI, EF remains the most important parameter in terms of clinical decision-making and overall prognosis [3, 20]. Among the higher-risk subset of patients with a reduced EF, optimising strategies to reduce residual risk are of paramount relevance [2, 7, 19, 21].…”
Section: Introductionmentioning
confidence: 99%
“…This stems from the fact that, although there are currently numerous parameters of potential interest in the prognostic assessment after an AMI, EF remains the most important parameter in terms of clinical decision-making and overall prognosis [3, 20]. Among the higher-risk subset of patients with a reduced EF, optimising strategies to reduce residual risk are of paramount relevance [2, 7, 19, 21].…”
Section: Introductionmentioning
confidence: 99%
“…Os primeiros trabalhos que adaptaram protocolos incrementais para a determinação do LAn em ER utilizaram uma razão de 1 min de esforço para 2 min de pausa entre os estágios do teste incremental 11,12 , enquanto que na presente pesquisa foi utilizada a razão 3 min para cada 1min de pausa. Apesar de outros trabalhos também terem adotado a mesma razão esforço/pausa abordada nos trabalhos originais [7][8][9][10]13,14 , a literatura sugere que quanto menor a razão esforço/pausa durante protocolos incrementais, maior a probabilidade de superestimação do LAn decorrente de uma maior eliminação dos metabólitos produzidos pelo metabolismo anaeróbio, possibilitando o alcance de cargas superiores 3,23 . Esta hipótese se confirma quando observamos que nos trabalhos em que foi utilizada a razão 1/2 (1 minuto de esforço para cada 2 minutos de repouso passivo), os voluntários alcançaram cargas próximas a 70 %1-RM durante o protocolo incremental, enquanto que na presente pesquisa, a desistência voluntária ocorreu nos estágios entre 25 e 35% de 1-RM, denotando a ocorrência de anaerobiose sob tais intensidades e impossibilitando a continuação do teste em intensidades superiores.…”
Section: Resultsunclassified
“…Apesar do modelo de exercícios resistidos (ER) ser amplamente utilizado para o desenvolvimento de força, potência e hipertrofia muscular, os benefícios no âmbito da saúde no combate e prevenção de diferentes doenças endócrino-metabólicas foi reconhecido apenas recentemente [1][2][3] . No entanto, podemos observar na literatura que mesmo nos estudos mais recentes, os métodos utilizados para avaliação e prescrição de treinamento nesta modalidade ainda são comumente baseados em testes de carga máxima ou uma repetição máxima (1-RM) [4][5][6] , não considerando outros aspectos fisiológicos importantes para a estimação de intensidades específicas de esforço, como por exemplo, variáveis metabólicas e hemodinâmicas.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Sijie T et al [38] showed no significant change in SBP and DBP after 15-week high intensity interval training in overweight young women. Ricardo Fontes-Carvalho et al [12] showed 8-weeks aerobic training after myocardial infarction did not significantly improve diastolic or systolic function parameters, although it was associated with a significant improvement in VO 2max . Despite much research, still cannot be said with certainty that aerobic interval training have a significant impact on the function of cardiovascular system.…”
Section: Pedagogics Psychologymentioning
confidence: 98%